Successful Management of Refractory Dialysis Independent Wegener’s Granulomatosis with Combination of Therapeutic Plasma Exchange and Rituximab - Malhotra, Sheetal (Indian J Hematol Blood Transfus, 2015)
Wegeners granulomatosis (WG) is an autoimmune, antineutrophil cytoplasmic antibody mediated necrotizing vasculitis involving renal, and upper and lower respiratory systems. Treatment relies on a combination of immunosuppressive drugs and tapering regimen of glucocorticoids. Therapeutic plasma exchange (TPE) has been recognized as a second line treatment. We report the successful use of TPE in combination with rituximab in achieving remission in a patient with WG (dialysis independent) not responding to conventional therapy.